2016
DOI: 10.2172/1235548
|View full text |Cite
|
Sign up to set email alerts
|

Low Carbon Grid Study: Analysis of a 50% Emission Reduction in California

Abstract: PrefaceThis study was funded by a variety of industry and foundation sources with the goal of understanding the impacts of a low-carbon grid in California. These organizations put together a Steering Committee to assemble the study team and guide the study process. The Low Carbon Grid Study (LCGS) put out three reports: 1) this one on grid operations, 2) an analysis by GE Energy on reliability impacts of the LCGS scenarios (Miller 2015), and 3) a capital cost analysis by JBS Energy of the LCGS scenarios (Marcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 5 publications
1
59
0
Order By: Relevance
“…To implement this curtailment method, we generated a regression model for the effective minimum generation of each NERC sub-region as a function of variable generation capacities. This regression is calculated using production cost model results from two WECC-wide studies (Lew et al 2013;Brinkman et al 2015), which are used as training data for the regression. This method of calculating the effective min-gen does not explicitly account for transmission between regions, nor does it account for upgrades in the transmission network that the model might build.…”
Section: Figure 6 Conceptual Depiction Of the Nldc-based Minimum Curmentioning
confidence: 99%
See 1 more Smart Citation
“…To implement this curtailment method, we generated a regression model for the effective minimum generation of each NERC sub-region as a function of variable generation capacities. This regression is calculated using production cost model results from two WECC-wide studies (Lew et al 2013;Brinkman et al 2015), which are used as training data for the regression. This method of calculating the effective min-gen does not explicitly account for transmission between regions, nor does it account for upgrades in the transmission network that the model might build.…”
Section: Figure 6 Conceptual Depiction Of the Nldc-based Minimum Curmentioning
confidence: 99%
“…Flexibility assessment has become an integral part of grid integration studies for renewables (GE Energy 2010;Lew et al 2013;EnerNex Corporation 2011;Bloom et al forthcoming;Venkataraman et al 2010;E3 2014;GE Energy 2014;Brinkman et al 2015). These studies use high-resolution models of grid operations (i.e., production cost models) to assess how the introduction of greater shares of variable renewable generation might affect production costs, emissions, and the mix of generated electricity.…”
Section: Introductionmentioning
confidence: 99%
“…In Phase 1 of the study, they found a worstcase scenario with curtailment as high as 11.9 percent. 47 But deploying a variety of mitigation options, most notably regional trade across the Western U.S., curtailment was dramatically reduced.…”
Section: A Diversify the Renewable Resource Portfoliomentioning
confidence: 99%
“…3) To what extent will renewables be curtailed with a higher (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) There are many different definitions of curtailment and there is no standardized way to measure it. 1 For the purposes of this article, we define curtailment as a reduction in the output of a wind or solar generator from what it could otherwise produce given available resources like wind or sunlight.…”
Section: Introductionmentioning
confidence: 99%
“…These results were aggregated to produce annual average hourly profiles (shown in Figure 1). The main analysis is based on a "standard scenario," which assumes moderate renewable energy build-out and accounts for planned closures of coal facilities and anticipated growth in natural gas generation (Brinkman 2015;Bloom et al 2016). In addition, a sensitivity analysis (presented in a later section) was conducted for cases with high and low percentages of renewable energy.…”
Section: Electricity Grid Profilesmentioning
confidence: 99%